Ultrasonic transducer kit for bacteria growth monitoring system - H. N. A. Salwa; Sundaraj, Kenneth, Prof. Madya; Azian Azamimi, Abdullah; Mohamed Zulkali, Mohamed Daud (Institute of Electrical and Elctronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/